β-CD-mediated Encapsulation Enhanced Stability and Solubility of Astaxanthin - Kim, S.Y., Hoseo University, Asan, Republic of Korea; Cho, E.A., Hoseo University, Asan, Republic of Korea; Yoo, J.M., Hoseo University, Asan, Republic of Korea; Cho, E.H., Hoseo University, Asan, Republic of Korea; Choi, S.J., Hoseo University, Asan, Republic of Korea; Son, S.M., Hoseo University, Asan, Republic of Korea; Lee, J.M., Hoseo University, Asan, Republic of Korea; In, M.J., Chungwoon University, Hongseong, Republic of Korea; Kim, D.C., Chungwoon University, Hongseong, Republic of Korea; Kim, J.H., Kongju National University, Kongju, Republic of Korea; Chae, H.J., Hoseo University, Asan, Republic of Korea (Applied biological chemistry, 2010)
To expand the industrial applications of astaxanthin in the food and cosmetic sectors, inclusion complexes (ICs) of astaxanthin were prepared with various types of cyclodextrins (CDs) and characterized by HPLC with respect to water-solubility and stability. Also, their characteristics were determined through SEM scanning electron microscopy and Furier transform infrared spectrometry. Among the various CDs, β-CD was selected as the host material for the inclusion of astaxanthin. The optimum ratio of astaxanthin and β-CD for IC formation was determined as 1:200. The water-solubility of the IC of astaxanthin and β-CD (As-β-CD) was enhanced up to 110-fold compared to free astaxanthin at pH 6.5 and 25℃. The stability of the β-CD-encapsulated astaxanthin against heat, light, and oxidation was greatly enhanced by over 7-9 folds compared to free astaxanthin. Furthermore, the β-CD-encapsulated astaxanthin had high stability even at 100℃. Compared to free astaxanthin, the IC formation of free astaxanthin greatly enhanced its stability under various storage conditions such as pH, temperature, ultraviolet irradiation, and the presence of oxygen.